UJI EFEKTIVITAS BEBERAPA INSEKTISIDA NABATI UNTUK MENGENDALIKAN ULAT GRAYAK (Spodoptera litura F.) (Lepidoptera : Noctuidae) DI LABORATORIUM - Mutiah Sari; Lahmuddin Lubis; Yuswani Yuswani Pangestiningsih (Universitas Sumatera Utara, 2013)
This Research was to study the effectiveness of some botanical insecticides in controling S. litura.This Research was done in Laboratory of Plant Pest, Faculty of Agriculture, University of NorthSumatera, Medan from September to October 2012. The method of this research was CompletelyRandomized Design Non Factorial with nine treatments. P0 (control), P1 (alamanda 250 gr / litre),P2 (alamanda 500 gr / litre), P3 (babadotan 250 gr / litre), P4 (babadotan 500 gr / litre), P5(kamboja 250 gr / litre), P6 (kamboja 500 gr / litre), P7 (mengkudu 250 gr / litre), P8 (mengkudu500 gr / litre) with two replications. The result showed that the most effective percentage mortalitywas found in treatment P4 (babadotan 500 gr / litre) (100%), followed by P2 (alamanda 500 gr /litre) (85%), P3 (babadotan 250 gr / litre) (80%), P6 (kamboja 500 gr / litre) dan P8 (mengkudu 500gr / litre) (75%) and less effective was found in P1(alamanda 250 gr / litre) and P5 (kamboja 250 gr/ litre) (45% and 50%). The most effective percentage of Forming pupae was found in P4(babadotan 500 gr / litre) (0%), followed by P2 (alamanda 500 gr / litre) and P3 (babadotan 250 gr /litre) (15% and 20%), and less effective at P1(alamanda 250 gr / litre) and P5 (kamboja 250 gr /litre) (55% and 50%), followed by P7 (mengkudu 250 gr / litre) (45%).